The Influence of Product Quality and Completeness on Consumer Rebuying in Irian Pasar Merah Medan - Atika Aini Nasution; Aan Nurhadi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Supermarket Irian is a retail company where this company provides basic daily needs such as cooking oil, food, drinks and other basic ingredients. With increasingly fierce competition in the retail sector, the Supermarket management is trying to maintain the quality and completeness of its products for the public with the aim of increasing a good impression for its consumers. The problem that occurs is how to maintain the quality and completeness of its products so that it can influence consumer repurchases and have an impact on time efficiency and a good impression for consumers who shop. Based on the description above, the research title is,